Pengaruh Analisis Jabatan, Beban Kerja dan Kompetensi Dimediasi Kepuasan Kerja Terhadap Kinerja Pegawai Sekretariat Daerah Provinsi Nusa Tenggara Timur - M. Billik, Marsella Alpiony; Langoday, Thomas Ola; Djuang, Gaudensius; Niha , Simon Sia; Sonbay, Yolinda Yanti; Gasparesz, Vincent (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Employee performance at the Regional Secretariat of East Nusa Tenggara Province is not optimal and is thought to be influenced by job analysis, workload and competency which is mediated by job satisfaction. This research aims to determine: 1) respondents' perceptions regarding job analysis, workload, competency, job satisfaction and performance of NTT Provincial Regional Secretariat employees; 2) the significance of the partial influence of job analysis, workload and respective competencies on job satisfaction of NTT Provincial Regional Secretariat employees; 3) the significance of the analysis of positions, workload and competency and job satisfaction, respectively, on the performance of employees of the Regional Secretariat of NTT Province; 4) the significance of job satisfaction in the analysis of positions, workload and competence of NTT Provincial Regional Secretariat employees. The method used in this research is a quantitative method using simple random sampling as many as 79 respondents. Data was collected using a questionnaire and analyzed using descriptive statistics and inferential statistics Partial Least Square (PLS). The results of descriptive statistical analysis show that respondents' perceptions of employee performance, job satisfaction and workload are in the good category, while job analysis is in the quite good category and competency is in the not good category. The results of inferential statistical analysis show value Adjusteed R-Square This research shows that the coefficient of determination for the job satisfaction variable is 0.397 or 39.7%, while the employee performance variable is 0.781 or the equivalent of 78.1%. 1) Job and competency analysis partially has a positive and significant effect on job satisfaction 2) Workload has a negative and significant effect on job satisfaction 3) Job analysis, workload, competency and job satisfaction partially has a positive and significant effect on employee performance, 4) Job satisfaction can significantly mediate the influence of job analysis, workload and competency on employee performance. Based on the research results, it is recommended to the Regional Secretary of NTT Province to pay more attention to competency factors which can be done through increasing and developing competency for all employees of the Regional Secretariat of NTT Province both through formal and non-formal education. Factor analysis of positions and workload is carried out by implementing the results of a comprehensive and structured analysis of positions and workload at the Regional Secretariat of East Nusa Tenggara Province to ensure that the roles, responsibilities of employees and workload as well as employee placement are carried out in accordance with educational qualifications and workload.